Amphibians and reptiles in the vicinity of Bulusan lake, Bulusan volcano natural park, Sorsogon, Philippines - Binaday, Jake Wilson B.; Amarga, Ace Kevin S.; Barrameda, Jr., Ernesto S.; Bonagua, Bobet Jan M. (2017)
A preliminary inventory of amphibians and reptiles from the vicinity of Bulusan Lake, Bulusan Volcano Natural Park is presented. So far, there is no existing account documenting the herpetofauna of this unique protected area. With this report, the researchers aim to provide baseline data on the identities of species of amphibians and reptiles existing in the natural park. A survey was conducted by employing visual encounter surveys. Specimens were identified in situ and were recorded by photographic documentation. The study resulted in the documentation of 26 species belonging to 24 genera in 14 families. This includes eight species of frogs, ten lizards, and eight snakes. The survey provides the first record of Aplopeltura boa (Blunthead Slug-eating Snake) from Luzon Island, and clarifies a previous point of confusion regarding species identification and use of the names Boiga drapiezii (White-spotted Cat Snake) and Boiga angulata (Philippine Blunt-headed Cat Snake) on Luzon. A novel account of a white-iris Tropidolaemus subannulatus (Northern Temple Pit Viper) is also presented. Considering the limited time and the confined area where the survey was conducted, a significant increase in this species list is expected as more surveys are conducted in the natural park focusing on different elevations and microhabitats. If future studies are permitted by the protected area managers, there is a high possibility of discoveringseveral novel and endemic species. (Author's abstract)